An examination of the influence of movies with smoking scenes on young adults’ attitude and risk perception toward smoking - Fang, Zhou (Kansas State University, 2012)
Cigarette smoking is one of the leading causes of preventable deaths in the U.S. and a global public health concern. The health effects have been severe among the youth. Smoking among the youth has been attributed to media. Movie in particular, is perhaps the most successful advertising on cigarette. Research shows that greater exposure to smoking in movies predicts increased likelihood of trying smoking. The purpose of this experimental study was to explore the relationships of smoking exposure in movies and young adults’ attitude, intention, and risk perception toward smoking. The theory of reasoned action (TRA) and the Attitude Accessibility Concept served were used in the study. The experiment was conducted at 70 Kansas State University students and examined the extent to which young adults’ memory/experience on smoking are triggered by watching smoking scenes; and whether young adults had different reactions based on the level of dosages of onscreen smoking. The results showed that the relationship of onscreen smoking and young adults’ memory/experience on smoking is not significant, as well as the relationship of media exposure and young adults’ attitude to smoke. However, the study found that nonsmokers contain considerable anti-smoking attitude and significant risk perception to smoke. The anti-smoking attitude is highly associated with the risk perception. The study presented theoretical implications, which includes the proposal to incorporate risk perception in the model of TRA, made recommendations to future anti-smoking campaigns targeted on young adults, and suggested areas of further research.
Keywords: Smoking; Movie; Young Adults; Memory; Intention; Risk Perception; Mass Communications (0708)